2014
DOI: 10.1016/j.jfluidstructs.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Motion-resonant modes of large articulated damped oscillators in waves

Abstract: Using a semi-analytical approach, we show that an articulated system of large damped oscillators in the open ocean can be resonated by incoming waves at multiple frequencies. As an application, energy extraction from the system is modelled when the oscillators are used as flap-type wave energy converters. A new parameter -the absorption efficiency -is introduced to analyse the performance of the system at resonance. This allows us to identify the occurrence of detrimental processes near the resonant frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…A similar resonant behavior at multiple frequencies has also been reported in the case of three inline OWSCs (see Ref. [27]). Note that the amplitude of rotation plotted in Fig.…”
Section: Pto Strategysupporting
confidence: 83%
“…A similar resonant behavior at multiple frequencies has also been reported in the case of three inline OWSCs (see Ref. [27]). Note that the amplitude of rotation plotted in Fig.…”
Section: Pto Strategysupporting
confidence: 83%
“…Because of their ability to capture energy with large efficiency, these converters have received significant attention in recent years, leading to analytical theories (Linton & McIver 2001;Mei, Stiassnie & Yue 2005) and experimental campaigns (Folley, Whittaker & van't Hoff 2007;Henry et al 2010). Renzi & Dias (2012, 2014 have developed a semi-analytical theory based on a hypersingular integral equation approach to investigate the hydrodynamic behaviour of a 'thin gate' in a channel and in open sea. Michele et al (2015) and Michele, Sammarco & d'Errico (2016a) have extended the theory of Renzi & Dias (2013) to the case of a single and multiple arrays of neighbouring OWSCs with finite thickness in open sea and in front of a vertical breakwater.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is believed that a WEC can absorb maximum energy at its resonant frequency. However, it is reported in the literature that an oscillating system, e.g., a flap-type WEC array [22] and a modular concept of flap-type WECs [17], may rarely harvest energy from ocean waves at some peculiar frequencies, but such an unexpected phenomenon has not been clearly explained. Sinha et al [8] investigated tuned arrays of heaving point absorbers and found that destructive interference may be observed at some specific sea state.…”
Section: Anti-resonancementioning
confidence: 99%
“…(5), with regard to the motion resonance in the theory of dynamical systems. The motion resonance of a system of oscillators in a wave has been investigated by Renzi and Dias [22]. The authors calculated the natural frequency of the system by solving the system of equations of motion when the damping terms (both radiation damping and PTO damping) and the excitation force are set to zero.…”
Section: Anti-resonancementioning
confidence: 99%